Major Vault Protein/Lung resistance related protein: a novel biomarker for inflammation and acute infections - Prof John Routsias; Dr Dionysia Marinou; Dr Maria Maurouli; Prof Athansios Tsakris; Prof Vassiliki Pitiriga (International Journal of Infectious Diseases)
Introduction: Vault particles are large cytoplasmic ribonucleoprotein particles that participate in inflammation. The aim of these study was to assess the diagnostic and the prognostic value of Major Vault Protein (MVP) in patients with inflammation, in order to unveil whether they could be used as biomarkers for infection or inflammation. We also aimed to compare of the diagnostic impact of MVP to other conventional methods like CRP or WBC measurement. Methods: CRP and MVP were measured, in 111 sera of 85 patients with inflammation and 26 healthy individuals using nephelometry and commercial ELISA assays. Statistical analysis was also conducted. Results: MVP levels were found elevated in patients with inflammation as compared to healthy individuals (t=7.12; p<0.0001). ROC analysis demonstrated that MVP and CRP present a similar high diagnostic accuracy with an AUC of 0.955 and 0.995 respectively, followed by WBC with an AUC of 0.805. In addition, the levels of MVP were higher in patients with inflammation of infectious etiology as compared to those with inflammation of non-infectious etiology (t=3.6, p= 0.0006). Analysis of serial samples of patients revealed that MVP was remarkable fell down during the first four days of infection, as a response to the antibiotic treatment, while CRP levels had a lower, insensitive, fall. Conclusion: ROC curves demonstrated that MVP has the potential to serve as a diagnostic biomarker for inflammation and infection. In addition, the levels of MVP may reflect the efficacy of antibiotic treatment.